Social anxiety symptoms and their relationship with suicidal ideation and depressive symptoms in adolescents: a prospective study - Chiu, K; Stringaris, A; Leigh, E (Wiley, 2024)
Background: Social anxiety disorder typically emerges in adolescence and its symptoms often co-occur with depression and suicidal ideation. It is important to understand whether social anxiety symptoms precede depression and suicidal ideation in youth. This study aimed to investigate the temporal associations between baseline social anxiety and later suicidal ideation and depressive symptoms in a community youth sample. Methods: The Wellcome Trust NSPN (Neuroscience in Psychiatry Network) study recruited 2397 youth aged 14-24 in the United Kingdom to participate in a prospective observational study. Participants were assessed for symptoms of social anxiety, generalised anxiety, depression and suicidal ideation at baseline, 1-year follow up, and 2-year follow-up. We conducted multiple linear regression analyses and mediation analyses to examine whether baseline social anxiety was associated with 2-year suicidal ideation and depressive symptoms (excluding suicide-related items), and whether these associations were mediated by 1-year depressive symptoms. The study was preregistered on the Open Science Framework. Results: Results from multiple linear regression analyses indicated that baseline social anxiety symptoms were associated with 2-year suicidal ideation (β = 0.07, p < .05, 95% CI [0.02, 0.12]) and 2-year depressive symptoms (β = 0.08, p < .05, 95% CI [0.02, 0.13]), after controlling for baseline predicted variable. Furthermore, 1-year depressive symptoms significantly mediated the relationship between baseline social anxiety symptoms and 2-year suicidal ideation (β = 0.04, 95% CI [0.02, 0.05]), and the relationship between baseline social anxiety symptoms and 2-year depressive symptoms (β = 0.06, 95% CI [0.03, 0.08]) after adjusting for age, sex, and other covariates. Conclusions: We found evidence that baseline social anxiety symptoms were associated with 2-year suicidal ideation and 2-year depressive symptoms via 1-year depressive symptoms in non-clinical adolescents. These results may have important implications for targeted psychological interventions.